Analysis of the influence of the minimum purchase lot on the stock control of an automobile company - Fenili, Gabriela Constantino; Araújo, Fernando de; Santos, Aline Gonçalves dos; Calife, Naiara Faiad Sebba; Rosa, Vanessa Aparecida de Oliveira (Brazilian Journal of Production Engineering, 2021)
The automobile sector has shown itself to be a strategic potential, considered a key activity in the industrialization process in Brazil (Kischner & Viegas, 2018). In this sense, as a justification for the study, it is highlighted that the planning/purchasing management process can represent a gain for the company, as it can minimize losses and avoid large volumes of fixed capital. In this aspect, this study aims to present a proposal for improvement to analyze the influence of negotiating a minimum lot of perishable items in an automobile industry. The research was based as quali-quantitative, applied, descriptive and a case study in an automobile company, using the ABC curve as strategic planning through inventory management. The results showed the 4 most discarded items in 2018 after analyzing the data collected and the size of the minimum purchase lots for each. It is concluded that the supplier who had a high minimum lot were the most discarded items, as these generate greater difficulty in purchasing management, which deals with several restrictions on a daily basis. Therefore, with so many barriers that influence the purchasing management process for perishable items, changing the minimum lot to the lowest negotiable value possible represents a gain for the company, as it allows the purchaser of the part to deal with routine changes and restrictions business with greater flexibility.
Keywords: Automotive Industry; Inventory Management; Minimum Lot.